Effects of Chlorpyrifos on Cholinesterase and Serine Lipase Activities and Lipid Metabolism in Brains of Rainbow Trout (Oncorhynchus mykiss). (30th July 2019) - Greer, Justin B; Magnuson, Jason T; Hester, Kirstin; Giroux, Marissa; Pope, Carey; Anderson, Timothy; Liu, Jing; Dang, Viet; Denslow, Nancy D; Schlenk, Daniel
Abstract: Chlorpyrifos is an organophosphorus insecticide that elicits acute toxicity through inhibition of acetylcholinesterase (AChE), leading to acetylcholine accumulation and prolonged stimulation of cholinergic receptors throughout the central and peripheral nervous systems. Previous studies have indicated that neurodevelopment may also be impaired through alternative pathways, including reduction of cyclic adenosine monophosphate (cAMP)-catalyzed downstream events. The upstream initiating events that underlie noncholinergic neurological actions of chlorpyrifos and other organophosphorus compounds remain unclear. To investigate the potential role of fatty acid signaling disruption as a mechanism of toxicity, lipid metabolism and fatty acid profiles were examined to identify alterations that may play a critical role in upstream signaling in the central nervous system (CNS). Juvenile rainbow trout were treated for 7 days with nominal chlorpyrifos concentrations previously reported to diminish olfactory responses (10, 20, and 40 μg/l). Although lethality was noted higher in doses, measured chlorpyrifos concentrations of 1.38 μg/l (nominal concentration 10 μg/l) significantly reduced the activity of AChE and two serine lipases, monoacylglycerol lipase, and fatty acid amide hydrolase in the brain. Reductions in lysophosphatidylethanolamines (16:0, 18:0, 18:1, and 22:6) derived from the phosphatidylethanolamines and free fatty acids (palmitic acid 16:0, linolenic acid 18:3, eicosadienoic acid 20:2, arachidonic acid 20:4, and docosahexaenoic acid 22:6) were also noted, suggesting that chlorpyrifos inhibited the metabolism of select phospholipid signaling precursors at sublethal concentrations. These results indicate that in addition to AChE inhibition, environmentally relevant chlorpyrifos exposure alters serine lipase activity and lipid metabolites in the trout brain, which may compromise neuronal signaling and impact neurobehavioral responses in aquatic animals.